The Influence of Learning Outside the Class on the Quality of Students' Al-Qur'an Memory at the Qur'an Elementary School Bahrusysyfa' Sukodono, Lumajang Regency, Indonesia - Syovinatus Sholicha; Imam Syaifudin; Azuan Syahiri; Arifatul Ma’ani; Eka Ismaya Indra Purnamanita; Bopel Wasianto; Eva Andriani (PT Inovasi Pratama Internasional, 2023)
Development of human resource capabilities including students in it is through a learning process. With this learning process students gain knowledge and skills, all of which students can acquire through the learning process, especially religious learning which has an important role in developing students' attitudes and spirituality. Basically a teacher should be able to implement a learning in which active interaction can be created between the teacher and students, fellow students and students with their environment. With learning like this it is hoped that students' understanding of religion can be better. On the other hand, a sense of belonging, loving the environment can also be embedded. Outdoor learning or learning outside the classroom indirectly reminds students that learning is not always done in the classroom. With learning like this it gives students room to add more memorization and provide the best quality for good Al Qur'an memorization. Because learning outside the classroom can create interactions between teachers and students, students and students as well as students and their environment. By trying to keep students happy to learn and memorize, of course, it will have an impact on students' understanding of murojaah memorizing the Koran, so that what is called competence in the quality of memorizing the Koran will be achieved. A teacher should be able to implement a learning in which an active and pleasant interaction is created between the teacher and students.